DUALISM OF JUDICIAL REVIEW IN INDONESIA: PROBLEMS AND SOLUTIONS - Chalid, Hamid A. (UI Scholars Hub, 2017)
Through the momentum of the third amendment of the 1945 Constitution of the Republic of Indonesia which was passed in 2001, Indonesia has officially adopted a dualistic judicial review system. Under such system, the authority to conduct judicial review is divided/spread to the two judicial organs, each with its own scope of review; namely, the Supreme Court/Mahkamah Agung reviews regulations below the level of Law (Undangundang), while the Constitutional Court/Mahkamah Konstitusi reviews the same against the Constitution (constitutional review). Seen from the theoretical and practical perspective adhered to by states which adopt the formation of the Constitutional Court (centered judicial review model), the system adopted by Indonesia is uncommon, and moreover it could be considered as an error in designing the judicial review system. This is in view of the fact that in states which have a Constitutional Court, the authority to conduct judicial review is concentrated / centered upon the Constitutional Court. Such division of authority under the two review regime (legal review and constitutional review) as practiced by Indonesia is not known (except for South Korea), neither in states which use the centralized judicial review model nor in those which use the distribution judicial review model. Such distribution is bound to disrupt the judicial review itself, as the authority to review is implemented by two different institutions with different review standard. Accordingly, in the final part of this research the author puts forward the proposition to centralize the authority to conduct judicial review in the Constitutional Court thus putting an end to the practice of dualistic judicial review which has been proven to be problematic and ensuring that the judicial review system in Indonesia can be reconstructed and placed upon the correct theoretical and practical basis.